Dynamics transitions at the outer vestibule of the KcsA potassium channel during gating - Raghuraman, H. (National Academy of Sciences, 2014)
In K(+) channels, the selectivity filter, pore helix, and outer vestibule play a crucial role in gating mechanisms. The outer vestibule is an important structurally extended region of KcsA in which toxins, blockers, and metal ions bind and modulate the gating behavior of K(+) channels. Despite its functional significance, the gating-related structural dynamics at the outer vestibule are not well understood. Under steady-state conditions, inactivating WT and noninactivating E71A KcsA stabilize the nonconductive and conductive filter conformations upon opening the activation gate. Site-directed fluorescence polarization of 7-nitrobenz-2-oxa-1,3-diazol-4-yl (NBD)-labeled outer vestibule residues shows that the outer vestibule of open/conductive conformation is highly dynamic compared with the motional restriction experienced by the outer vestibule during inactivation gating. A wavelength-selective fluorescence approach shows a change in hydration dynamics in inactivated and noninactivated conformations, and supports a possible role of restricted/bound water molecules in C-type inactivation gating. Using a unique restrained ensemble simulation method, along with distance measurements by EPR, we show that, on average, the outer vestibule undergoes a modest backbone conformational change during its transition to various functional states, although the structural dynamics of the outer vestibule are significantly altered during activation and inactivation gating. Taken together, our results support the role of a hydrogen bond network behind the selectivity filter, side-chain conformational dynamics, and water molecules in the gating mechanisms of K(+) channels.